Lysine-63-linked ubiquitination is required for endolysosomal degradation of class I molecules - Duncan, Lidia M (2006)
MHC class I molecules display peptides from endogenous and viral proteins for immunosurveillance by cytotoxic T lymphocytes (CTL). The importance of the class I pathway is emphasised by the remarkable strategies employed by different viruses to downregulate surface class I and avoid CTL recognition. The K3 gene product from Kaposi's sarcoma-associated herpesvirus (KSHV) is a viral ubiquitin E3 ligase which ubiquitinates and degrades cell surface MHC class I molecules. We now show that modification of K3-associated class I by lysine-63-linked polyubiquitin chains is necessary for their efficient endocytosis and endolysosomal degradation and present three lines of evidence that monoubiquitination of class I molecules provides an inefficient internalisation signal. This lysine-63-linked polyubiquitination requires both UbcH5b/c and Ubc13-conjugating enzymes for initiating mono- and subsequent polyubiquitination of class I, and the clathrin-dependent internalisation is mediated by the epsin endocytic adaptor. Our results explain how lysine-63-linked polyubiquitination leads to degradation by an endolysosomal pathway and demonstrate a novel mechanism for endocytosis and endolysosomal degradation of class I, which may be applicable to other receptors.